Measurement of the Higgs boson mass with H→γγ decays in 140 fb-1 of √s=13 TeV pp collisions with the ATLAS detector - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Czurylo, Marta; Rio, Fernando del; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Klassen, Martin; Mkrtchyan, Tigran; Ott, Philipp; et al. (Physics letters, 2023)
The mass of the Higgs boson is measured in the H→γγ decay channel, exploiting the high resolution of the invariant mass of photon pairs reconstructed from the decays of Higgs bosons produced in proton-proton collisions at a centre-of-mass energy √s=13 TeV. The dataset was collected between 2015 and 2018 by the ATLAS detector at the Large Hadron Collider, and corresponds to an integrated luminosity of 140 fb-1. The measured value of the Higgs boson mass is 125.17±0.11(stat.)±0.09(syst.) GeV and is based on an improved energy scale calibration for photons, whose impact on the measurement is about four times smaller than in the previous publication. A combination with the corresponding measurement using 7 and 8 TeV pp collision ATLAS data results in a Higgs boson mass measurement of 125.22±0.11(stat.)±0.09(syst.) GeV. With an uncertainty of 1.1 per mille, this is currently the most precise measurement of the mass of the Higgs boson from a single decay channel.
Online verfügbar: 10. November 2023
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Im Titel ist "-1" bei "fb-1" hochgestellt
The ATLAS collaboration: G. Aad, L.M. Baltes, F. Bartels, M. Czurylo, F. Del Rio, S. Dittmeier, M. Dunford, S. Franchino, T. Junkermann, M. Klassen, T. Mkrtchyan, P.S. Ott, D.F. Rassloff, S. Rodriguez Bosca, C. Sauer, A. Schöning, H.-C. Schmitz-Coulon, V. Sothilingam, R. Stamen, P. Starovoitov, L. Vigani, S.M. Weber, M. Wessels, J. Zinsser [und 2930 weitere]
Gesehen am 30.06.2025